1992
DOI: 10.1113/jphysiol.1992.sp019132
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and kinetic properties of alpha 4 beta 2 neuronal nicotinic acetylcholine receptors expressed in Xenopus oocytes.

Abstract: SUMMARY1. Co-injection of RNA synthesized from cloned neuronal acetylcholine receptor (nAChR) subunits (a4 and fl2) in Xenopus oocytes produced functional receptors. In macroscopic voltage-clamp experiments, the agonist-induced current exhibited a strong inward rectification.2. Voltage jumps from + 50 mV to more negative potentials produced relaxations of the agonist-induced current with a single exponential time course. The relaxation rate constant was only weakly voltage dependent.3. At the single-channel le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
(66 reference statements)
10
41
0
Order By: Relevance
“…9, A-J; Table 3). Consistent with previous reports (Charnet et al, 1992;Kuryatov et al, 1997;Figl et al, 1998), the rat ␣4␤2 wild-type channels displayed multiple conductance states in 0 mM added Ca 2ϩ (Fig. 9, A-D; Table 3).…”
Section: Receptorsupporting
confidence: 80%
“…9, A-J; Table 3). Consistent with previous reports (Charnet et al, 1992;Kuryatov et al, 1997;Figl et al, 1998), the rat ␣4␤2 wild-type channels displayed multiple conductance states in 0 mM added Ca 2ϩ (Fig. 9, A-D; Table 3).…”
Section: Receptorsupporting
confidence: 80%
“…The largest WT conductance state was similar to the 46 pS value for recombinantly expressed human á4â2 nicotinic receptors (Buisson et al 1996). The smaller WT conductance state (34 pS) was similar to a previous value (34 pS) for rat á4â2 nicotinic receptors expressed in oocytes (Charnet et al 1992 In the single patch without 49 pS openings, we assigned a percentage area of zero to the 49 pS component and 100% to the 34 pS component. The WT channels spent 60 ± 11 % (mean ± s.e.m., n = 6 patches) of the total open time in the 34 pS state and 40 ± 11 % (n = 6) of the total open time in the 49 pS state.…”
Section: Mutations Affect Single-channel Conductancementioning
confidence: 87%
“…Therefore, it is likely that at some types of receptors 5_HT acts on the agonist binding sites and at others within the ionic channel. This would resemble the effects of hexamethonium, which appears to inhibit muscle AChRs competitively (Rang & Rylett, 1984) but neuronal receptors non-competitively (Charnet et al 1992). However, we have reported that in oocytes expressing the á2â4 neuronal AChR subtype the ACh-current is inhibited by 5_HT in a noncompetitive and voltage-dependent fashion (Garc úa-Colunga & Miledi, 1994, which is similar to the effects of 5_HT on chromaffin cells (Vijayaraghavan et al 1993) and on á7 homomeric AChR (Palma et al 1997).…”
Section: Effects Of Serotonergic Agents On Muscle Achrsmentioning
confidence: 99%